Enhanced Antioxidation and UV-Absorption Ability of Industrial Lignin via Promoting Phenolic Contents and Hydrophilicity - He, Lili; Guo, Haiping; Lu, Jiayue; Liu, Qiyu; Qiu, Xueqing (ACS omega, 2025)
Lignin possesses unique natural antioxidation and UV-absorption abilities, making it a promising ingredient for sunscreen. However, the industrial lignin produced from pulping or bioethanol production generally shows low efficiency due to the limited phenolic hydroxyl content and poor compatibility with sunscreen, respectively. To address this issue, a molten salt hydrate treatment process was carried out for the selective cleavage of ether bonds in industrial lignin. After treatment, a 2-fold increase in phenolic hydroxyl content was observed, and lignin antioxidation efficiency was improved. The intermolecular forces of lignin in water measured by an atomic force microscope showed a significant decrease from −1.46 to 0.46 mN/m, suggesting an efficient increase in lignin hydrophilicity, which promoted lignin compatibility with sunscreen. We converted industrial lignin into colloidal balls, which improved compatibility and dispersion in the cream and more than tripled the sun protection factor compared to the direct addition of industrial lignin.